Sustainability and large corporations. (2016) - McIntyre, Michael L.; Caputo, Tullio; Murphy, Steven A.
This paper reports the results of a content analysis conducted on the annual reports and corporate social responsibility reports of the members of the Dow Jones Industrial Average. The content analysis explored how these corporations address sustainability matters in these reports, and compared these with the intergenerational conception of sustainability expressed in Brundtland and Khalid's (1987) landmark work - referred to as Our Common Future. By intergenerational conception of sustainability, we mean thinking of sustainability in terms of the current generation acting responsibly with respect to the impact that their activities have on the society and the environment in order to ensure that they are not compromising the ability of future generations to meet their needs. The findings reveal that two of the 30 corporations explicitly referred to the Brundtland definition while three others mentioned intergenerational rights more generally. Furthermore, although the term sustainability appears frequently in the documents that were reviewed, it was often difficult to determine with a degree of exactitude what the users mean by it. A number of corporations espoused their adherence to a 'three pillars approach' and touted incremental gains made year over year. Finally, many referred to external agencies to add legitimacy to their efforts.